Golden Supplications for Children From the Quran and Sunnah - Abdul Malik Mujahid; Compiled by Abdullah Alkhizri, Sheikh (Lahore Darussalam, 2013)
Golden Supplications for Children from the Quran and Sunnah A beautifully illustrated dua book for you and your children. Honorable readers, there is not a person in this world who is not facing some sort of difficulty or problems. Anyone can strengthen their bond with Allah simply by making supplications to him. This Islamic book of supplications has been especially put together for your children to help them memorise the most important supplication to help them through they daily life
Includes Colored Illustrations
Keywords: Golden Supplications for Children